An evaluation of China’s agricultural green production: 1978–2017 - Liu, Yifang; Sun, Dongsheng; Wang, Huijuan; Wang, Xiaojuan; Yu, Guiqin; Zhao, Xiujuan (Journal of cleaner production, 2020)
Green development and low-carbon economy play important roles to achieve sustainable society. Since agricultural production is the foundation of the Chinese national economy, agricultural green production acts as the driving force in green economy development, as well as a prerequisite to realize green behavior and sustainable ecology. Different from traditional agricultural production, the idea of agricultural green production also put many factors including economy, environment, and social development into comprehensive consideration. It provides the future directions of China’s agriculture. This research aims to systematically sort the agricultural green production goals from five dimensions: supply capacity, resource utilization, environment quality, ecosystem maintenance, and farmers’ lives. An agricultural green production assessment index system was constructed based on national agricultural census data indicators. Furthermore, the gap between China’s agricultural green production status and target value, as well as the vertical and spatial evolution of agricultural green production levels in China have been determined empirically relying on the data from three national agricultural censuses and additional statistical data from national statistical yearbooks and coefficient manuals. Moreover, key recommendations were provided for path optimizing and China’s agricultural green production upgrading.